Pengaruh Efikasi Diri, Prestasi Belajar dan Perencanaan Karir Terhadap Kesiapan Kerja Mahasiswa Jurusan Manajemen FEB Unsrat: The influence of self-efficacy, learning achievement and career planning on work readiness of students majoring in management at FEB Unsrat - Sumampouw, Pamella (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2024)
Work readiness is defined as the ability that comes from oneself with little or no outside help to seek, obtainand adjust work in accordance with what is needed and desired by the individual. The purpose of this study was todetermine the effect of self-efficacy, learning achievement and career planning on the work readiness of studentsmajoring in management FEB Unsrat. The population in this study were FEB Unsrat Management students class of2019 totaling 290 people and determining the sample using the slovin formula and obtained a sample of 75 peoplewith a precision level set at 10%. The analytical tool in this study used SPSS version 26 which was used to analyzethe independent variable and the dependent variable. The results of this study found that self-efficacy has a positivebut insignificant effect on work readiness, learning achievement has a significant positive effect on work readiness,career planning has a significant positive effect on work readiness.